Ovomucoid epitope‐specific repertoire of IgE, IgG4, IgG1, IgA1, and IgD antibodies in egg‐allergic children. Issue 10 (1st June 2020) - Suprun, Maria; Getts, Robert; Grishina, Galina; Tsuang, Angela; Suárez‐Fariñas, Mayte; Sampson, Hugh A.
Abstract: Background: Egg‐white ovomucoid, that is, Gal d 1, is associated with IgE‐mediated allergic reactions in most egg‐allergic children. Epitope‐specific IgE levels have been correlated with the severity of egg allergy, while emerging evidence suggests that other antibody isotypes (IgG1, IgG4, IgA, and IgD) may have a protective function; yet, their epitope‐specific repertoires and associations with atopic comorbidities have not been studied. Methods: Bead‐based epitope assay (BBEA) was used to quantitate the levels of epitope‐specific ( es )IgA, es IgE, es IgD, es IgG1, and es IgG4 antibodies directed at 58 (15‐mer) overlapping peptides, covering the entire sequence of ovomucoid, in plasma of 38 egg‐allergic and 6 atopic children. Intraclass correlation (ICC) and coefficient of variation (CV) were used for the reliability assessment. The relationships across es Igs were evaluated using network analysis; linear and logistic regressions were used to compare groups based on egg allergy status and comorbidities. Results: BBEA had high reliability (ICC >0.75) and low variability (CV <20%) and could detect known IgE‐binding epitopes. Egg‐allergic children had lower es IgA1 ( P = .010) and es IgG1 ( P = .016) and higher es IgE ( P < .001) and es IgD ( P = .015) levels compared to the atopic controls. Interestingly, within the allergic group, children with higher es IgD had decreased odds of anaphylactic reactions (OR =0.48, P = .038). Network analysis identified most associations between es IgE with either es IgG4 or es IgD; indicating that IgE‐secreting plasma cells could originate from either sequential isotype switch from antigen‐experienced intermediate isotypes or directly from the IgD + B cells. Conclusions: Collectively, these data point toward a contribution of epitope‐specific antibody repertoires to the pathogenesis of egg allergy. Abstract : Egg‐allergic children have lower levels of epitope‐specific (es) IgA1 and es IgG1 but higher es IgE and es IgD compared to the atopic controls. Within the allergic group, children with higher es IgD antibodies have decreased odds of anaphylactic reactions. Network analysis identifies most associations between es IgE with either es IgG4 or es IgD, indicating potentially different origins of IgE.